The Dynamics of Turnover Intentions: Emotional Intelligence, Thriving at Work, and Career Adaptability in an Indonesian Banking Sector - Arti, Miladani Binti; Kurniawati, Desi Tri (Universitas Mercu Buana, 2024)
Objectives: The research focuses on the high turnover intention ratio in the East Java banking sector. The aim is to explore the role of emotional intelligence (EI) in reducing employee turnover by considering thriving at work (TW) and career adaptability (CA). This research highlights the importance of emotional intelligence and its positive effects through training programs to reduce Turnover Intentions (TOI).Methodology: This research used an explanatory quantitative method involving 105 frontline employees. The sample used a saturated sampling method. Data was collected through questionnaires distributed to all frontliners, with 103 questionnaires returned. The data were analyzed using the SEM-PLS method.Finding: The result found that EI does not directly influence frontline employees' desire for TOI. Nonetheless, employees with high levels of EI tend to thrive more at work, reducing their desire for TOI. The ability to develop and adapt in the work environment can be a more significant factor in reducing TOI.Conclusion: EI is important in reducing the TOI of Bank frontline employees. Employees with high EI can better develop and adapt to a stressful work environment, reducing TOI and increasing well-being and commitment to self-development.